Oxidation Desulphurization of Heavy Naphtha Improved by Ultrasound Waves - Jima, Bariq Bahmman; Majeed, Najwa Saber (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The oxidation desulphurization assisted by ultrasound waves was applied to the desulphurization of heavy naphtha. Hydrogen peroxide and acetic acid were used as oxidants, ultrasound waves as phase dispersion, and activated carbon as solid adsorbent. When the oxidation desulphurization (ODS) process was followed by a solid adsorption step, the performance of overall Sulphur removal was 89% for heavy naphtha at the normal condition of pressure and temperature. The process of (ODS) converts the compounds of Sulphur to sulfoxides/ sulfones, and these oxidizing compounds can be removed by activated carbon to produce fuel with low Sulphur content. The absence of any components (hydrogen peroxide, acetic acid, ultrasound waves and activated carbon) from the ODS process leading to reduce the performance of removal, hydrogen peroxide was the most crucial factor. The ultrasound waves increase the dispersion of carbon, water and oil phase, promotes the interfacial mass transfer, and this leads to accelerates the reaction. The ultrasound waves did not affect the chemical or physical properties of the fuel. The chemical analysis of treated fuel oil showed that <1% of the hydrocarbon fuel compounds were oxidized in the ODS process. In this work, desulphurization by oxidation is the main mechanism was tested with several parameters that effects desulphurization efficiency such as sonication time (5-40) min, activated carbon (0.01-0.5) gm, hydrogen peroxide (1-30) ml, and acetic acid (1-15) ml. It was found that the hydrogen peroxide amounts lead to increase oxidation rates of Sulphur compounds so, the desulphurization efficiency increases. The optimum amounts of oxidants are 10 ml hydrogen peroxide per 100 ml of heavy naphtha. Increasing the amount of acid catalyst lead to increase Sulphur removal, it was found that7.5 ml acid per 10 ml oxidant was the optimum amount. Activated carbon as a solid adsorbent and reaction enhancer with 0.1gm weight was found as the optimum amount for 100 ml heavy naphtha. Increasing sonication time lead to increase desulphurization rate, it was found that (10 min) is the optimum period. By applying the optimum parameters 89% of sulfur can be removed from heavy naphtha with 598.4 ppm Sulphur content.